Treatment of oral candidiasis using Photodithazineï¿½- mediated photodynamic therapy in vivo - Carmello, Juliana Cabrini [UNESP]; Alves, Fernanda [UNESP]; Basso, Fernanda G. [UNESP]; De Souza Costa, Carlos Alberto [UNESP]; Bagnato, Vanderlei Salvador; Mima, Ewerton Garcia De Oliveira [UNESP]; Pavarina, Ana Clï¿½udia [UNESP] (Public Library of Science (PLoS), 2016)
This study evaluated the effectiveness of antimicrobial photodynamic therapy (aPDT) in the treatment of oral candidiasis in a murine model using Photodithazineï¿½ (PDZ). This model of oral candidiasis was developed to allow the monitoring of the infection and the establishment of the aPDT treatment. Six-week-old female mice were immunosuppressed and inoculated with C. albicans to induce oral candidiasis. PDZ-mediated aPDT and nystatin treatment were carried out for 5 consecutive days with one application per day. The macroscopic evaluation of oral lesions was performed. After each treatment, the tongue was swabbed to recover C. albicans cells. Viable colonies were quantified and the number of CFU/ml determined. The animals were sacrificed 24 hours and 7 days after treatment and the tongues were surgically removed for histological analysis and analysis of inflammatory cytokines expression (IL-1, TNF-α and IL-6) by RT-qPCR. Data were analyzed by two-way ANOVA. PDZ-mediated aPDT was as effective as Nystatin (NYS group) in the inactivation of C. albicans, reducing 3 and 3.2 logs10 respectively, 24 h after treatment (p<0.05). Animals underwent PDZ-mediated aPDT showed complete remission of oral lesions, while animals treated with NYS presented partial remission of oral lesions in both periods assessed. Histological evaluation revealed mild inflammatory infiltrate in the groups treated with aPDT and NYS in both periods assessed. The aPDT induced the TNF-α expression when compared with the control (P-L-) (p<0.05), 24 h and 7 days after treatment. In summary, the murine model developed here was able to mimic the infection and PDZ-mediated aPDT was effective to treat mice with oral candidiasis.